Investigation of the interaction of two parallel shifted cracks in plate bending adjusted for their closure - Dalyak Taras (Theoretical and Applied Mechanics, 2019)
The problem of interaction of two parallel shifted cracks in plate bending is considered. The cracks closure has been investigated in the classical two-dimensional statement, using the model of smooth contact along a line. The influence of the relative position of cracks and of the contact of their edges on the forces and moment intensity factors has been studied by the singular integral equations method.